Analysis of Students' Error In Solving Probability Problem: A Case Study In Guangxi - Yuxian Huang; Ying Zhou; Yong Li (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2021)
This research analyzes the types and reasons of students' mistakes in solving probability and the analysis statistics problems by qualitative research method. The subjects were 20 senior High school students from a senior high school in Guangxi, China. The data were collected through the student diagnostic test. The students' answers were analyzed by using O'Connel's analysis. The results show that the proportion of misunderstood problems is 48.18% at the largest proportion, and the proportion of computational errors is next, accounting for 36.36%. The proportion of procedural errors is the least, accounting for 15.45%. As we all know, there are many reasons for the above mistakes., so teachers can find some solutions to overcome these mistakes.